Extracellular vesicles—connecting kingdoms - Woith, Eric; Fuhrmann, Gregor; Melzig, Matthias F. (International Journal of Molecular Sciences, 2019)
It is known that extracellular vesicles (EVs) are shed from cells of almost every type of cell or organism, showing their ubiquity in all empires of life. EVs are defined as naturally released particles from cells, delimited by a lipid bilayer, and cannot replicate. These nano-to micrometer scaled spheres shuttle a set of bioactive molecules. EVs are of great interest as vehicles for drug targeting and in fundamental biological research, but in vitro culture of animal cells usually achieves only small yields. The exploration of other biological kingdoms promises comprehensive knowledge on EVs broadening the opportunities for basic understanding and therapeutic use. Thus, plants might be sustainable biofactories producing nontoxic and highly specific nanovectors, whereas bacterial and fungal EVs are promising vaccines for the prevention of infectious diseases. Importantly, EVs from different eukaryotic and prokaryotic kingdoms are involved in many processes including host-pathogen interactions, spreading of resistances, and plant diseases. More extensive knowledge of inter-species and interkingdom regulation could provide advantages for preventing and treating pests and pathogens. In this review, we present a comprehensive overview of EVs derived from eukaryota and prokaryota and we discuss how better understanding of their intercommunication role provides opportunities for both fundamental and applied biology.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Archaea; Cross-kingdom RNAi; Eukaryota; Extracellular vesicles; Interkingdom communication; Prokaryota